Revealing English to Indonesian Humor Translation Techniques in Despicable Me Movie - Anwar, Rima Ayu Lailita (Language Horizon: Journal of Language Studies, 2024)
This research examines translation, specifically the translation of jokes in the Despicable Me film. The goal of this research is to determine the translation techniques employed to preserve the universal humor words in the target text. The study objectives are fulfilled using qualitative methodologies. To get accurate information, the researcher observed both the English and Indonesian versions of the film, identifying humorous terms and classifying them based on translation techniques. This study classifies the data using Molina and Albir's (2002) translation technique theories. The data indicate that the majority of universal humor terms were translated literally, while the remainder were translated using generalization, modulation, borrowing, description, and reduction techniques.